IMPLEMENTASI PEMBELAJARAN MEMBATIK DALAM MATA PELAJARAN SENI BUDAYA PADA KELAS XII DI SMA NEGERI 1 VII KOTO SUNGAI SARIAK - Yosi Folastri; Ezriani (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This descriptive qualitative study aims to describe and analyze the implementation of hand-drawn batik (batik tulis) learning and the artwork outcomes of grade XII students at SMA Negeri 1 VII Koto Sungai Sariak, who previously only received theoretical lessons. The research subjects included the school principal, the arts teacher, and grade XII students, with data gathered through observation, interviews, and documentation. The results indicate that this practice-based learning was conducted over 8 meetings (90 minutes per session) through preparation, designing, transferring designs to mori fabrics, wax-canting, Remasol coloring, and wax-removal. The collective final products were tablecloths featuring the Minangkabau local wisdom motif of the "Makan Bajamba" tradition combined with supporting ornaments. Despite being beginners, this direct practice successfully enhanced students' creativity, discipline, teamwork, and structural understanding of local cultural philosophy through functional and highly artistic works.